Pseudo-Outbreak of Imipenem-Resistant Acinetobacter baumannii Resulting from False Susceptibility Testing by a Rapid Automated System - Tsakris, Athanassios (American Society for Microbiology, 2000)
Introduction of the Vitek GNS-506 susceptibility testing cards in the Hippokration General Hospital, Thessaloniki, Greece, resulted in an apparently high prevalence of imipenem-resistant Acinetobacter baumannii. When 35 of these isolates were further tested by disk diffusion, broth microdilution, and agar dilution assays, 32 were imipenem sensitive by all tests and three were sensitive or intermediate, depending on the method. The pseudoresistant acinetobacters did not form a genetically homogeneous group. It is suggested that the detection of imipenem-resistant A. baumannii isolates by this system should be confirmed by an additional susceptibility test.